2013
DOI: 10.1182/blood-2013-03-491555
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide corrects impaired mesenchymal stem cell function in inducing tolerogenic DCs in patients with immune thrombocytopenia

Abstract: Key Points The impaired function of MSCs in proliferation ability and in inducing tolerogenic DCs may play a role in the pathogenesis of ITP. The effect of THD in correcting dysfunctions of MSCs may suggests a therapeutic potential of THD in ITP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
1
13
0
1
Order By: Relevance
“…Targets of these key miRNAs showed enrichment in enzyme activities related to GO processes (activation of caspase activity; regulation of caspase, peptidase, and endopeptidase activities) in both ITP stages. These activities, especially those related to caspase, have been reported to be associated with ITP [37, 38]. Decreased expression of TRAIL, caspase-8, and caspase-3 in megakaryocytes after culture in plasma from patients with ITP, consistent with the inhibition of megakaryocyte apoptosis and reduced production of platelets, has been reported [39].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Targets of these key miRNAs showed enrichment in enzyme activities related to GO processes (activation of caspase activity; regulation of caspase, peptidase, and endopeptidase activities) in both ITP stages. These activities, especially those related to caspase, have been reported to be associated with ITP [37, 38]. Decreased expression of TRAIL, caspase-8, and caspase-3 in megakaryocytes after culture in plasma from patients with ITP, consistent with the inhibition of megakaryocyte apoptosis and reduced production of platelets, has been reported [39].…”
Section: Discussionsupporting
confidence: 54%
“…Decreased expression of TRAIL, caspase-8, and caspase-3 in megakaryocytes after culture in plasma from patients with ITP, consistent with the inhibition of megakaryocyte apoptosis and reduced production of platelets, has been reported [39]. Another study suggested that decreased caspase-8 and caspase-10 expression is related to the effects of thalidomide on mesenchymal stem cells, which may contribute to the pathogenesis of ITP [38]. …”
Section: Discussionmentioning
confidence: 65%
“…These concerns were raised largely due to the observation of dysfunctionality and attenuated immunosuppressive properties of MSCs derived from patients with autoimmune ailments [13][14][15], although other studies failed to find such defects in related immune disorders [16][17][18]. Genome wide association studies have shown that single nucleotide polymorphisms (SNPs) predispose individuals to develop autoimmune disorders [19] and SNPs in the indoleamine 2,3-dioxygenase (IDO) gene have been shown to be associated with systemic sclerosis [20].…”
Section: Introductionmentioning
confidence: 99%
“…The thalidomide modulated MSCs from ITP patients induced mature DCs to become tolerogenic DCs. And the induction of tolerogenicity in DCs by MSCs was dependent on the expression of TIEG1in DCs[130]. Furthermore, recent experiments clearly documented the inhibitory effect irradiation on proliferation of MSCs, but does not impair the immunosuppressive capacity of BM-MSCs in vitro and thus might increase the safety of MSC-based cell products in clinical applications[131].…”
mentioning
confidence: 98%